Perdidas na esquina: lutas de representações e composições visuais das travestis no jornal Lampião da Esquina - RJ (1978-1981) - Rubbi, Gustavo de Souza (2024)
In 1978, the Brazilian press reported the possibility of a liberalization of the national political context. With expectations of a democratic opening, the newspaper Lampião da Esquina emerged at this juncture. Produced and edited by homosexuals, the periodical circulated between April 1978 and July 1981, publishing thirty-eight regular editions and three extra editions. Around twenty-eight editions presented, through reports, opinion articles, interviews and letters, the theme of gender and the body of transvestites. In this sense, in order to understand the characteristics and processes of identity construction of transvestites, the present work aims to investigate the representational trajectories and visual compositions of these identities in the newspaper Lampião da Esquina. In this way, we analyzed how the political and graphic projects produced by editors and collaborators influenced the narratives about transvestites. To achieve the proposed objective, the dissemination, disputes and tensions surrounding transvestite compositions were analyzed. We seek to highlight the tensions present in the different ways of representing these identities and the way in which the newspaper contributed to the reaffirmation of old stereotypes and the construction of new ones regarding transvestites. We mainly used Dona Haraway's gender perspectives, Chartier's concept of representations, and Nicholas Mirzoeff's concept of visuality. The study of the representations and visualities created by the editors regarding transvestites made it possible to reveal that during the publications the editors grouped the multiple identities under the concept of homosexuals. This work also revealed that the periodical acted by producing a certain imaginary practice of transvestites and attributed behaviors and characteristics to these identities. Furthermore, the study of the fountain's political project favored the composition of an image/representational picture of transvestites during the 1970s and 1980s.